Application of pseudocontinuous arterial spin labeling perfusion imaging in children with autism spectrum disorders - Ye, Fang; Du, Lei; Liu, Bing; Gao, Xinying; Yang, Aocai; Liu, Die; Chen, Yue; Lv, Kuan; Xu, Pengfei; Chen, Yuanmei; Liu, Jing; Zhang, Lipeng; et al. (Frontiers in Neuroscience, 2022)
Introduction: Pseudocontinuous Arterial Spin Labeling (pCASL) perfusion imaging allows noninvasive quantification of regional CBF as part of a multimodal MRI protocol. This study aimed to compare regional CBF in autism spectrum disorders (ASD) individuals with their age-matched typically developing (TD) children using pCASL perfusion Imaging. Methods: This cross-sectional study enrolled 17 individuals with ASD and 13 TD children. All participants underwent pCASL examination on a 3.0 T magnetic resonance imaging (MRI) scanner. Children in two groups were assessed for clinical characteristics and developmental profiles using Autism Behaviour Checklist (ABC) and Gesell development diagnosis scale (GDDS), respectively. We compared CBF in different cerebral regions of ASD and TD children. We also assessed the association between CBF and clinical characteristics / developmental profile. Results: Compared with TD children, individuals with ASD demonstrated a reduction in CBF in the left frontal lobe, the bilateral parietal lobes, and the bilateral temporal lobes. Within the ASD group, CBF was significantly higher in the right parietal lobe than in the left side. Correlation analysis of behaviour characteristics and CBF in different regions showed a positive correlation between body and object domain scores on the ABC and CBF of the bilateral occipital lobes, and separately, between language domain scores and CBF of the left frontal lobe. The score of the social and self-help domain was negatively correlated with the CBF of the left frontal lobe, the left parietal lobe, and the left temporal lobe. Conclusions: CBF was found to be negatively correlated with scores in the social and self-help domain, and positively correlated with those in the body and object domain, indicating that CBF values are a potential MRI-based biomarker of disease severity in ASD patients. The ﬁndings may provide novel insight into the pathophysiological mechanisms of ASD.